Self-potential near surface and subsurface Investigation for soil and ground water in Farming land nearby Quldara Village /Northeast Kirtuk/Nothern Iraq - Dhahir K. ALI (Tikrit Journal of Pure Science)
Near surface soil and subsurface self-potential investigations were carried out in farming land nearby Quldara Village/Northeast Kikruk town about 15 km at area about 63000 m2. Nine soil samples has been taken to determine texture, organic materials percentage , PH, electric conductivity Ec and electric resistivity in the laboratory. Geophysical Self-potential method  survey applied through six lines, the separation was teen meters between the electrodes of the employed instrument  and teen measurement points has been taken , each line was  100 m. The self-potential data processed and presented as profiles and contour maps. Soil analysis proved that it is composed of homogeneous sandy clayey silt with normal content of organic materials and salt with moderate acidity, it is suitable for crop growin. Self-potential data interpretations indicated that the possibility of ground water in the study area